Cultural Immersion Program as a Potential Live Laboratory for Applied English Students in Indonesia - Reswari, Girindra Putri Ardana; Kalimanzila, James (Vocational College of Universitas Diponegoro, 2020)
Applied English students as vocational future graduates must be prepared to be ready to work in international atmosphere directly after they are graduates. One of the most essential skills that should be learned is intercultural interaction. There are two problems that should be answered in this research. First, how is the previous implementation of CIP in Indonesia? Second is why CIP can be used as live laboratory for applied English students? The purpose of this research is to discuss and analyze the success of CIP in Indonesia and its potentials of Cultural Immersion Program (CIP) in becoming the live laboratory for Applied English students. Reflected on the increasing number of International Students in Indonesia, many Cultural Immersion Programs (CIP) held by some institutions to build interaction between local society and international students. This research is a qualitative study. The data is collected by asking 30 international students. This study found that the implementation of CIP in Indonesian is seen as something effective to learn about Indonesia by the international students who ever joined the program. Another finding is CIP could be a miniature of the working place for international tourism since it also has intercultural interaction as well as has same goal and principle with international tourism. Therefore, it could be a potential live laboratory for Applied English students in Vocational School at the university level.